1979
DOI: 10.1002/jrs.1250080204
|View full text |Cite
|
Sign up to set email alerts
|

Spectres Raman de Résonance de Dérivés Parasubstitués de l' Azobenzène

Abstract: Resonance Raman spectra of twenty parasubstituted azobenzene derivatives are compared, enabling a more complete assignment of bands to be made. Since all the spectra are rather similar, the various ring substituents are not resonance Raman active, and all the observed bands can be assigned to vibrational modes of the aromatic rings and to the azo group itself. Frequency shifts in the PhN stretching region are opposite to those expected based on delocalization along the PhNNPh moiety. From the complexity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…corresponded to the torsion of the methyl groups and the modes above at 930 cm -1 were associated with, as suggested by Lorriaux et al [55], the C-H in-plane bending and the Ph-N=N-Ph in-plane bending vibrations. The intensities of the out-ofplane C-H and the torsion C-C vibrations calculated between 940 cm -1 and 990 cm -1 were too low to be visible in the spectra.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…corresponded to the torsion of the methyl groups and the modes above at 930 cm -1 were associated with, as suggested by Lorriaux et al [55], the C-H in-plane bending and the Ph-N=N-Ph in-plane bending vibrations. The intensities of the out-ofplane C-H and the torsion C-C vibrations calculated between 940 cm -1 and 990 cm -1 were too low to be visible in the spectra.…”
Section: Resultssupporting
confidence: 65%
“…Hence, we can conclude that the coupling between the phenyl-N stretching and the CH in-plane bending mode 9a′ is weak for this mode in comparison to the mode around 1159 cm -1 . Lorriaux et al [55] have suggested linking the bond orders of the N-phenyl bonds of different azobenzene derivatives to the observed shift of this band. With this consideration, a high bond order would indicate a short bond length and a high wave number.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…This last absorption band is overlapped by the ν 19a (CdC) stretching vibration of the para-substituted phenyl rings. [37][38][39][40] The PM-IRLD spectrum recorded on the 5% DR1 doped PMMA film irradiated during approximately 1 h is presented in Figure 3B. As seen on the figure, the signal-to-noise ratio of this difference spectrum is remarkable, even though the ∆A for the strongest band is only -0.03.…”
Section: Methodsmentioning
confidence: 99%